Influence of the composition of nutrient media on the productivity and biological activity of the strain of entomopathogenic fungus Beauveria bassiana - I. E. Sharapova (Аграрная наука Евро-Северо-Востока)
The productivity and biological activity of the entomopathogenic fungus Beauveria bassiana (F-145) strain during the liquid-phase cultivation on various substrates for developing a biopesticide in its native form was analyzed (the research was carried out in 2019). For submerged cultivation, by-products from dairy and beer production (milk whey and brewing spent grain liquor) were used as components of the nutrient medium with addition of diesel fuel (DF) and Tween-80 as inducers of biological activity. It has been established, that the productivity of the strain on industrial by-product substrates was 1.5-2 times higher than on the Czapek medium. A high yield of a mycelial biomass with a titer of 108 -1010 CFU/ml was shown in a 5-day suspension based on a mixture of milk whey and brewing spent grain liquor. The biological activity of the culture suspension of the strain was determined. It was shown that the nematicidal activity of Beauveria bassiana strain with regard to nematodes of the Rhabditis sp. was largely manifested in a suspension obtained on a mixed medium with the addition of inducers. Ninety per cent death at mobile nematode stages was registered within one or two days of test-organism incubation. A complex nutrient medium composition containing by-products and inducers contributed to the preservation of the biological activity of the strain. The strain nematicidal activity was established at the level of 67-80 per cent with a titer of 106 -107 CFU/ml when the suspension was stored for 67 days.